2022
DOI: 10.3389/fcvm.2021.797976
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Ventricular Premature Complex Is Associated With Cardiovascular Mortality

Abstract: BackgroundVentricular premature complex (VPC) is one of the most common ventricular arrhythmias. The presence of VPC is associated with an increased risk of heart failure (HF).MethodWe designed a single-center, retrospective, and large population-based cohort to clarify the role of VPC burden in long-term prognosis in Taiwan. We analyzed the database from the National Cheng Kung University Hospital-Electronic Medical Record (NCKUH-EMR) and NCKUH-Holter (NCKUH-Holter). A total of 19,527 patients who underwent 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Although decreased mortality in the treatment group may be partially due to the well-known benefits of beta blockers in heart failure and sudden cardiac death, our study also demonstrated the consistent benefits in lowering mortality rate of patients without heart failure in the treatment group, as shown in Figures 3, 4. While concerning similar but statistically significant difference in PVC burdens between treatment and non-treatment groups in low-burden PAC sub-cohort, in our recent data (15), moderate (1,000-10,000 beats per 24 h) and high burdens (>10,000 beats per 24 h) of PVCs had higher risk of cardiovascular death than low-burden PVC group (Find and Gray's competing risk model adjusted HR = 1.48, 95% CI = 1.09-2.01, p < 0.05; HR = 1.70, 95% CI = 1.06-2.71, p < 0.05). However, our data showed no difference in all-cause mortality.…”
Section: Discussionsupporting
confidence: 49%
“…Although decreased mortality in the treatment group may be partially due to the well-known benefits of beta blockers in heart failure and sudden cardiac death, our study also demonstrated the consistent benefits in lowering mortality rate of patients without heart failure in the treatment group, as shown in Figures 3, 4. While concerning similar but statistically significant difference in PVC burdens between treatment and non-treatment groups in low-burden PAC sub-cohort, in our recent data (15), moderate (1,000-10,000 beats per 24 h) and high burdens (>10,000 beats per 24 h) of PVCs had higher risk of cardiovascular death than low-burden PVC group (Find and Gray's competing risk model adjusted HR = 1.48, 95% CI = 1.09-2.01, p < 0.05; HR = 1.70, 95% CI = 1.06-2.71, p < 0.05). However, our data showed no difference in all-cause mortality.…”
Section: Discussionsupporting
confidence: 49%
“…The study design was validated and described in our previous studies. 3 , 9 , 10 , 11 The study protocol and clinical data were approved by the institutional review board of National Cheng‐Kung University Hospital (approval number B‐ER‐108‐290). Informed consent was not required because the database enrolled in this study was deidentified.…”
Section: Methodsmentioning
confidence: 99%
“… 2 Moderate and high burdens of PVC also increase the risk of cardiovascular mortality compared to that of low burden of PVC. 3 , 4 In addition to cardiovascular complications, PVC is also associated with ischemic stroke. 5 Some case reports have demonstrated that PVC can trigger atrial fibrillation (AF) via intracardiac tracing.…”
mentioning
confidence: 99%
“…Despite having a different pathophysiological mechanism, syncope can be a marker of arrhythmic events, and be involved in an increased risk of death. 6 The study period was from January 2014 to December 2016. Patients who underwent Holter during hospitalization or after hospital discharge (up to 30 days) in a database with 4179 exams were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Apesar de ter um mecanismo fisiopatológico diferente, a síncope pode ser um marcador de eventos arrítmicos, e estar envolvido em um risco aumentado de morte. 6 O período do estudo foi de janeiro de 2014 a dezembro de 2016. Foram identificados pacientes que se submeteram ao Holter durante a internação ou após a alta hospitalar (até 30 dias) em um banco de dados com 4179 exames.…”
Section: Delineamento Do Estudounclassified